Human resource management (Hrm) practices in construction organizations: A review - Bukhari, H. (Praise Worthy Prize S.r.l, 2021)
Management and behavioural practices of an organization highlight the importance of Human Resource Management (HRM) to its performance. The objective of this review is to identify the HRM practices of construction industry acknowledged by researchers from the year 2007 to 2019. Databases related to human resource (HR) in the construction industry were referred, where 125 papers were selected, out of which 79 papers were found relevant. The decade has been observed having a proper flow of the research and the sequence of which undergoes as it starts from leadership styles and attitudes then considers the employee-related dimensions. Onwards the research steered its direction towards linking the practices that are mutually beneficial for organizations and employees. Towards the end of the decade, the competitive success factors and organizational norms and practices were engrossed. With this knowledge, a framework has been introduced showing how different HRM practices associate with each other. Â© 2021 Praise Worthy Prize S.r.l. - All rights reserved.